Faktor-Faktor yang Mempengaruhi Pengungkapan Intellectual Capital Pada Perusahaan Property dan Real Estate - Soraya faradina (Faculty of Economic and Business, 2015)
The purpose of this research is to find out the effect of firm age, firm size, leverage, profitability and concentration of ownership on intellectual capital disclosure. The sample of this study is from property and real estate firm that listed on Indonesian Stock Exchange from 2010 until 2014. This research using purposive sampling method, to determine the sample of this research with 80 companies as population and 16 companies as sample. This research using multiple linear regression analyzed method by SPSS program version 22 for windows. Partially, the results of this research indicate that only firm size has an effect on intellectual capital disclosure, while firm age, leverage, profitability and concentration of ownership do not have an effect on intellectual capital disclosure. The result also indicates that firm age, firm size, leverage, profitability and concentration of ownership simultaneously have an effect on intellectual capital disclosure.DOI: 10.15408/ess.v5i2.2350